(Invited) Ferroelectric-HfO2 Devices: Physics and Applications. (8th September 2020) - Kobayashi, Masaharu
Abstract : Newly discovered ferroelectric-HfO2 opens up the new opportunities of low-power, high-speed, and high-density nonvolatile memories. In this paper, our recent research progresses of ferroelectric-HfO2 memories are introduced: nonvolatile SRAM (NVSRAM) for smart power management in IoT applications, ferroelectric tunnel junction (FTJ) for ultimately small memory device, and ferroelectric FET (FeFET) with novel channel material for high-density memory. Challenges and opportunities of each device technology are discussed.